2023
DOI: 10.3390/ijerph20021214
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Large-Scale Social and Behavior Change Communication Intervention in the Lake Zone Region of Tanzania on Knowledge, Attitudes, and Practices Related to Stunting Prevention

Abstract: Background: Large-scale social and behavioral change communication (SBCC) approaches can be beneficial to achieve improvements in knowledge, attitudes, and practices (KAP). Addressing Stunting in Tanzania Early (ASTUTE) included a significant SBCC component and targeted precursors to stunting including KAP related to maternal and child health, antenatal care, WASH, childhood development, and male involvement. METHODS: Baseline, midline, and endline surveys were conducted for a total of 14,996 female caregivers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…These findings echo those from other SBC interventions. For example, a Tanzania study that explored the impact of social behaviour change interventions on knowledge, attitude and practice related to key MNCH+N indicators identified many changes that corresponded with SBC programming in the region and also provided support for the value of large social behaviour change interventions 32. Similarly, a study in Ghana found that SBC intervention increased knowledge on maternal health 33…”
Section: Discussionmentioning
confidence: 99%
“…These findings echo those from other SBC interventions. For example, a Tanzania study that explored the impact of social behaviour change interventions on knowledge, attitude and practice related to key MNCH+N indicators identified many changes that corresponded with SBC programming in the region and also provided support for the value of large social behaviour change interventions 32. Similarly, a study in Ghana found that SBC intervention increased knowledge on maternal health 33…”
Section: Discussionmentioning
confidence: 99%
“…Intervensi dalam perubahan perilaku tidak hanya terbatas dari pemberian edukasi saja, namun diperlukan adanya komunikasi atau konseling, dan praktik langsung yang dilakukan pada sebuah kegiatan (Darajat et al, 2022). Melalui media komunikasi edukasi, pesan kesehatan dapat tersampaikan secara optimal (Dearden et al, 2023;Triatmaja et al, 2023). Selanjutnya praktik diperlukan untuk meningkatkan keterampilan seseorang.…”
Section: Hasil Monitoring Dan Evaluasiunclassified
“…To achieve the goals outlined, the SBCC stunting strategy must be implemented through a staged method based on the SBCC model and planning principles [35]. This method is founded on evidence and a vision for a participative and long-term effort that incorporates all parties involved in dealing with stunting [36]. The steps that can be taken can be seen in Table 1 below:…”
Section: Political and System Levelmentioning
confidence: 99%